Endobronchialer Ultraschall - Gompelmann, Daniela; Eberhardt, Ralf; Herth, Felix (Der Radiologe, 2010)
Endobronchial ultrasound (EBUS), one of the most important advances in pneumology in recent years, provides visualization of bronchial walls and parabronchial structures, extending the diagnostic spectrum of bronchoscopic techniques. Two different techniques are available: radial endobronchial ultrasound and the technique of ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). Due to a high diagnostic informative value, low effort and low risk, EBUS has become incorporated into routine practice in pulmonary centers. Thus endobronchial ultrasound has proved to be of increasing importance in the diagnosis of mediastinal mass and staging of lung cancer. EBUS-TBNA is particularly useful for the evaluation of hilar and mediastinal lymph nodes in cases of lung neoplasms with a sensitivity of 88% and specificity of 100%. EBUS therefore plays an important role in the new interdisciplinary guidelines on "prevention, diagnostics, therapy and aftercare of lung cancer".